The Influence of Reading Aloud Islamic Stories on The Spiritual Intelligence of Children Aged 5—6 in RA Wadas Kelir, South Purwokerto - Zubaedah, Siti; Hafidz, Nur; Riska Nofianti, Farhati (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Spiritual intelligence is the privilege of every individual related to human behavior or actions. Human action begins in early childhood. One of the media to hone children's spiritual intelligence is through reading Aloud Islamic children's storybooks, books presenting stories of prophets, stories of friends, and exemplary values for children. Reading aloud Islamic children's storybooks have the characteristics of simple language 2-4 sentences, attractive illustrations, and easy to reflect content. The purpose of this study was to determine the effect of reading Aloud Islamic children's storybooks on the spiritual intelligence of children aged 5-6 years in Raudhatul Athfal Wadas Kelir Purwokerto Selatan. This study uses quantitative data analysis with simple regression, using the SPSS 25 application to conclude, collecting data by distributing questionnaires to 20 guardians of students. The results showed that there was a significant 83.2% effect of reading aloud Islamic children's storybooks on the spiritual intelligence of children aged 5-6 years in Raudhatul Athfal Wadas Kelir, South Purwokerto. The resulting data obtained a calculated value of 9,450, while the table with N = 20 with a significance level of 0.05 is 1,910, meaning count > count. From here, the conclusion Ho is rejected and Ha is accepted. The impact of this research on simple linear regression data, namely Y = 11, 264+860 X is positive. The contribution of Islamic children's storybooks to the spiritual intelligence of early childhood is 83.2% and 16.8% is influenced by other factors.